Ancient Biographies: Trace Element Analysis to Investigate Provenance and Transportation Mechanisms of Late Bronze Age Glass. (5th September 2018) - Kemp, Victoria; McDonald, A.; Shortland, A.J.
Abstract : LA-ICPMS analysis was carried out on a scaraboid blue glass bead (Hunterian Museum Glasgow, D.1921.39) excavated from Tomb 27 in Gurob, in the Southern Fayum region of Egypt. Gurob is known to have been the site of a "harem palace" established in the reign of Tuthmosis III (1479-1425 BC). The tomb was located at the northernmost point of the New Kingdom cemetery and was undisturbed, containing the remains of seven females and two children, and was dated by the excavators to between the reigns of Amenophis I (1525-1504 BC) and Tuthmosis III. The glass scarab was coloured by copper and trace element values of La, Cr, Ti and Zr exhibited compositional consistency with glasses from Mesopotamia, rather than from Egypt. Therefore, the glass scarab represents a rare example of Mesopotamian glass to be discovered in Egypt, in addition to being some of the earliest glass found. The finds support iconographic references in the Hall of the Annals at Karnak to the import of early glass into Egypt. The implication is that these beads represent luxury items transported into Egypt by high-ranking foreign women perhaps in connection with the Gurob harem palace.